Sound of hope : the story of Possum Trot [videorecording (DVD)] - Johnson, Sean Philip (Angel Studios, 2024)
Inspired by the powerful true story, "Sound of Hope: The Story of Possum Trot" follows Donna and Reverend Martin as they ignite a fire in the hearts of their rural church to embrace kids in the foster system that nobody else would take. By doing the impossible--adopting 77 children--this East Texas community proved that with real, determined love, the battle for America's most vulnerable can be won.